PENGGUNAAN BAHASA INDONESIA DALAM DUNIA DIGITAL DAN EFEKNYA TERHADAP TATA BAHASA - Ahmad Sulthoni,; Susi Febrian,; Cindy Fitria Harum Ningtyas,; Muhammad Royhan,; Salsabila Khoirunnisa, (Jurnal Cakrawala Ilmiah, 2025)
The focus of this study is the influence of the digital era and globalization on the use of Indonesian among the younger generation, consisting of students, college students, and active social media users. The main objective of this study is to find changes in language structure, perceptions of standard language, and linguistic and cultural issues that arise as a result of the spread of digital content, social media, and e-commerce. This research focuses on language use on social media platforms such as TikTok, WhatsApp, and Shopee, and includes social media users of various ages, schools, and urban communities. The methodology used includes descriptive qualitative studies, quantitative surveys, hermeneutics, and systematic literature reviews (SLRs), with data models including interviews, observations, online questionnaires, and digital content analysis. The results of the study show that the use of Indonesian is increasingly eroded by the dominance of foreign languages ​​and informal styles. This can have a negative impact on students' mental health and character and reduce their understanding of standard language. However, the younger generation still realizes the importance of maintaining Indonesian. Therefore, language literacy strategies and digital education are very important to ensure the sustainability of the language amidst the flow of globalization.